Ninian Pinkney papers - Pinkney, Ninian, 1811-1877.
Correspondence, speeches, articles, notes, medical papers, photographs, and other papers relating primarily to Pinkney's tours of naval duty, surgical cases in Peru, his observations on the Mexican War and U.S. Civil War, his plan to reorganize the U.S. Army Medical Corps, and his interest in politics. Correspondents include George Bancroft, Henry Clay, Samuel Hambleton, Matthew C. Perry, Gideon Welles, and Pinkney's wife, Mary H. Pinkney.
Naval surgeon.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Bancroft, George, -- 1800-1891 -- Correspondence; Clay, Henry, -- 1777-1852 -- Correspondence; Hambleton, Samuel, -- 1812-1886 -- Correspondence; Perry, Matthew Calbraith, -- 1794-1858 -- Correspondence; Pinkney, Mary H. -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; United States. -- Army. -- Medical Corps; United States. -- Navy; Medicine -- Practice -- Peru; Mexican War, 1846-1848.; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 19th century; Surgeons